Bypassing primary healthcare facilities for maternal healthcare in North West Ghana: socio-economic correlates and financial implications - Valeria Avoayea Amoro; Gilbert Abotisem Abiiro; Kennedy A. Alatinga (BMC, 2021)
Abstract Background Bypassing primary health care (PHC) facilities for maternal health care is an increasing phenomenon. In Ghana, however, there is a dearth of systematic evidence on bypassing PHC facilities for maternal healthcare. This study investigated the prevalence of bypassing PHC facilities for maternal healthcare, and the socio-economic factors and financial costs associated with bypassing PHC facilities within two municipalities in Northwestern Ghana. Methods A quantitative cross-sectional design was implemented between December 2019 and March 2020. Multistage stratified sampling was used to select 385 mothers receiving postnatal care in health facilities for a survey. Using STATA 12 software, bivariate analysis with chi-square test and binary logistic regression models were run to determine the socio-economic and demographic factors associated with bypassing PHC facilities. The two-sample independent group t-test was used to estimate the mean differences in healthcare costs of those who bypassed their PHC facilities and those who did not. Results The results revealed the prevalence of bypassing PHC facilities as 19.35 % for antenatal care, 33.33 % for delivery, and 38.44 % for postnatal care. The municipality of residence, ethnicity, tertiary education, pregnancy complications, means of transport, nature of the residential location, days after childbirth, age, and income were statistically significantly (p < 0.05) associated with bypassing PHC facilities for various maternal care services. Compared to the non-bypassers, the bypassers incurred a statistically significantly (P < 0.001) higher mean extra financial cost of GH₵112.09 (US$19.73) for delivery, GH₵44.61 (US$7.85) for postnatal care and ₵43.34 (US$7.65) for antenatal care. This average extra expenditure was incurred on transportation, feeding, accommodation, medicine, and other non-receipted expenses. Conclusions The study found evidence of bypassing PHC facilities for maternal healthcare. Addressing this phenomenon of bypassing and its associated cost, will require effective policy reforms aimed at strengthening the service delivery capacities of PHC facilities. We recommend that the Ministry of Health and Ghana Health Service should embark on stakeholder engagement and sensitization campaigns on the financial consequences of bypassing PHC facilities for maternal health care. Future research, outside healthcare facility settings, is also required to understand the specific supply-side factors influencing bypassing of PHC facilities for maternal healthcare within the study area.